Kontribusi Customer Relationship Management terhadap Retensi Pelanggan: Kasus pada Coffeeshop Saga Kahwa - Amelia, Ratih; Windi Ayuni, Tyus; Hou, Amin; Harnjo, Eddy; Bhastary, Manda Dwipayani (JURNAL EKUIVALENSI, 2025)
This study supposed to analyze the contribution of Customer Relationship Management (CRM) to customer retention in independent coffee shop businesses, using Coffeeshop Saga Kahwa as a case study. Amidst intense competition and the challenge of maintaining customer loyalty, CRM implementation becomes a crucial strategy to drive repeat visits and build long-term customer relationships. The research applies a quantitative approach with Structural Equation Modeling–Partial Least Square (SEM-PLS) as the analytical technique. CRM is measured through four dimensions: customer orientation, technology-based CRM, knowledge management, and service quality, while customer retention is evaluated based on indicators of loyalty and repurchase intention. The results show that all four CRM dimensions have a positive and significant effect on customer retention, with an R Square value of 0.803, indicating strong combined influence. These findings imply that the strategic application of CRM, even at the small business level such as independent coffee shops, can significantly enhance customer loyalty and business competitiveness.